Digital Transformation in Energy Sector: Impact of Mandatory Cashless Payments on Customer Satisfaction - Angga Yuandri; Yunita Hasrina (Journal Of Economic Cluster, 2025)
Public sector digitalization has driven the transformation to cashless payment systems to enhance operational efficiency. However, mandatory technology adoption in emerging economies often faces adaptation challenges affecting service perception. This study aims to analyze the impact of mandatory cashless payments on customer satisfaction in the energy retail sector. Using a quantitative approach, data were gathered from 80 MyPertamina users in the satellite region of South Sumatra. Simple linear regression analysis reveals that the cashless system significantly and positively impacts customer satisfaction (R2 = 0.700). The findings confirm that digital transaction efficiency and security are primary satisfaction drivers, despite the mandatory nature of the system. Theoretically, this study contributes to technology adoption literature by proving that reliable digital infrastructure is key to customer loyalty in emerging economies. Managerially, it suggests integrating customer education and application stability to mitigate digital transition barriers in the energy sector.